Manajemen Pelayanan Publik - Fikri, Muhammad Akbar Rijalul; Tjenreng, Muhammad Baharuddin Zubakhrum (Jurnal PKM Manajemen Bisnis, 2025)
This research discusses public service management in Indonesia with a focus on service quality, management implementation and performance measurement. Through a qualitative approach, this research reviewed various literature sources that identified factors that influence the quality of public services, such as technology, human resources and service processes. It found that the implementation of digital technology and e-government can improve efficiency and transparency, while the development of HR competencies through training is also very important. However, challenges such as inequality between urban and rural areas, cumbersome bureaucracy, and lack of professionalism of state apparatus are still obstacles. The research also emphasizes the importance of community participation in public service improvement. Overall, public service management in Indonesia requires continuous efforts in bureaucratic reform, improving the quality of human resources, and utilizing technology to realize services that are more efficient, transparent, and responsive to community needs.